Underage Marriage Reviewing from the Law Number 1, 1974 & PMA Number 11, 2007 (A Case Study in Soppeng District) - Muhammad Iqbal; Nidaul Islam (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2021)
This study aims to determine the effectiveness of implementing of the Law of Republic of Indonesia Number 1, 1974 concerning marriage and the Regulation of the Minister of Religion Number 11 of 2007 concerning Marriage Registration, especially the minimum age limit in marriage. This research is a qualitative descriptive study which describe underage marriages in Soppeng Regency. The approach used are the syar’i and the juridical approach. The results show that the understanding of the people of Soppeng Regency to Law No. 1/1974 about the age requirement for marriage recognized. But some people do not obey these rules, due to lack of education, economic crush, and promiscuity. The existence of Law Number 1 of 1974, especially the minimum age requirement for marriage, is still not effective. As the results of the data got in various Offices of Religious Affairs (KUA) and at the Religious Courts of Soppeng Regency, the number of prospective brides who are not old enough to marry. They apply for dispensation at the Religious Courts and the Panel of Judges grants their request to marry.